Therapeutic Exercises for Spine Aberrations, According to the Kinematic Analysis, in Improving the Motor Capabilities of Children (6-9 Years) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Physical deviations that are closely related to technological development helped to the emergence of diseasesresulting from inactivity and lack of movement, So therapeutic exercise is one of the means to help improvethe strength of pupils by using the means of assistance as a means of treating deviations of the spine suchas (rubber ropes, medical balls, stick and various sponge pieces). The purpose of therapeutic exercises isto help the child return to activity and life as quickly as possible, reduce pain and increase the flexibility ofjoints and muscle elasticity. Therefore, the researcher used the one-group experimental curriculum (tribalafter test), and the research community was identified from the 150 students and students of the 2018-2019school year, and 22 students were identified. Their age of (6-9) years in the deliberate way, as the therapeuticprogram was implemented which includes therapeutic exercises for (6) weeks by (12) therapeutic unitsand the time of the therapeutic unit (35) minutes, and concluded the researcher that the therapeutic unitsfollowed by the researcher to reduce deviations in the column.